Kebijakan Pendidikan Pemerintahan Orde Lama Serta Pengaruhnya terhadap Pendidikan Islam di Indonesia - Sismawati Sismawati; Muhammad Taraki; Kasful Anwar US; Sya'roni Sya'roni (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
This paper discusses the education policies of the Old Order government and their influence on Islamic education in Indonesia. This paper aims to find out in depth about the Old Order government, the education policies of the Old Order government and the influence of Old Order education policies on Islamic education in Indonesia. During the Old Order era, Islamic education began to be fought for reform with the publication of various policies regarding the improvement of Islamic education, including compulsory Madrasah Learning (MWB). Indonesia became independent from Dutch colonial rule on August 17, 1945. The period of President Soekarno's reign, which spanned from 1945 to 1966, was referred to as the Old Order to differentiate it from the subsequent Order led by President Soeharto. In particular, the Old Order government's policy of paying attention to Islamic boarding schools and madrasas only began when the Central Indonesian National Committee Working Body (BP KNIP) 22 on December 27 1945 submitted recommendations to the government. The aim of this research is to understand the concept of government during the Old Order, and its influence on education in Indonesia. The research method used is a basic theory method that uses data from materials that are library research, where the author reads and studies books or literature related to the problem being studied. Regardless of the aspect The positive and negative sides of all the policies issued, it can be said that the development of madrasas is a brave effort by Islamic education to maintain its existence and identity while metamorphosing with the times.